Studi Tentang Akuntabilitas, Transparansi Pengelolaan Keuangan Sekolah Dan Kualitas Layanan Pendidikan Di SMA Negeri Kabupaten Kaur Yang Terakreditasi A, B, Dan C - Khoirunnisa Nurul Habibatulloh; Slamet Widodo; Trisna Murni (UNIB Press, 2022)
AbstractThe purpose of this study is to describe accountability, transparency of school financial, and quality of education services. The variables in this study are service quality, accountability, and transparency. The population in this study were schools that were accredited A, B, and C. The number of samples in this study was 93 people consisting of teachers, TU (Administration), committee administrators, and students from schools accredited A, B, and C. Methods of collection The sample in this study used questionnaires, interviews, and documentation. The study concluded are quality of education services at accredited A schools is in the very quality category with an average perception value of 4.32. The accountability of the financial management of the accredited school is in the accountability level with an average perception value of 4.02. The transparency of the financial management of the A-accredited school is in transparency with an average perception value of 4.19. Quality of Education Services for schools accredited B is in the very quality category with an average perception value of 4.32. The financial management accountability of accredited B schools is in the very accountable category with an average perception value of 4.44. The transparency of the financial management of accredited B schools is in the very transparent category with an average perception value of 4.47. Quality of Education Services for C-accredited schools is in the quality category with an average perception value of 4.06. The accountability for the management of the C-accredited school financial category is accountable with an average perception value of 4.08. The transparency of the financial management of the C-accredited school is in transparency with an average perception value of 4.17. Keyword: Servive Quality, Accountability, Transparency Abstrak Tujuan penelitian ini adalah untuk mendeskripsikan akuntabilitas, transparansi keuangan sekolah, dan kualitas layanan pendidikan. Variabel dalam penelitian ini adalah kualitas pelayanan, akuntabilitas, dan transparansi. Populasi dalam penelitian ini adalah sekolah yang terakreditasi A, B, dan C. Jumlah sampel dalam penelitian ini adalah 93 orang yang terdiri dari guru, TU (Administrasi), pengurus komite, dan siswa dari sekolah terakreditasi A, B, dan C. Metode Pengumpulan Sampel dalam penelitian ini menggunakan angket, wawancara, dan dokumentasi. Hasil penelitian menyimpulkan bahwa mutu pelayanan pendidikan pada sekolah terakreditasi A berada pada kategori sangat bermutu dengan nilai persepsi rata-rata sebesar 4,32. Akuntabilitas pengelolaan keuangan sekolah yang terakreditasi berada pada tingkat akuntabilitas dengan nilai persepsi rata-rata 4,02. Transparansi pengelolaan keuangan sekolah terakreditasi A berada pada transparansi dengan nilai persepsi rata-rata 4,19. Mutu Pelayanan Pendidikan untuk sekolah terakreditasi B berada pada kategori sangat bermutu dengan nilai persepsi rata-rata sebesar 4,32. Akuntabilitas pengelolaan keuangan sekolah terakreditasi B berada pada kategori sangat akuntabel dengan nilai persepsi rata-rata 4,44. Transparansi pengelolaan keuangan sekolah terakreditasi B berada pada kategori sangat transparan dengan nilai persepsi rata-rata 4,47. Kualitas Layanan Pendidikan untuk sekolah terakreditasi C berada pada kategori kualitas dengan nilai persepsi rata-rata 4,06. Pertanggungjawaban pengelolaan keuangan sekolah kategori terakreditasi C dapat dipertanggungjawabkan dengan nilai persepsi rata-rata 4,08. Transparansi pengelolaan keuangan sekolah terakreditasi C berada pada transparansi dengan nilai persepsi rata-rata 4,17. Kata Kunci: Kualitas Pelayanan, Akuntabilitas, Transparansi